State control mechanisms as means of improving the quality of public services of local self-government bodies - Kruhlov, Vitalii; Volkova, Nataliia; Krasnykov, Yevgen; Alieksieienko, Iryna; Sokhatiuk, Larysa (DIXI, 2024)
The article deals with the state control mechanisms and their role in improving the quality of public services provided by local self-government bodies. The aim of the article is to identify key state control mechanisms, opportunities for improving the level of public services of local self-government bodies, and provide recommendations for improving the system of state control. Different state control mechanisms were studied, including inspections, performance evaluation, financial audit, quality standards, legal oversight, and citizen feedback mechanisms. Contextual analysis, comparison, and graphic methods were used as research methods. Satisfaction with services in the EU countries was determined by different areas of public services. The study emphasizes the importance of state control in promoting transparency, accountability, and continuous improvement in local government service delivery. The results of the study demonstrate ways of optimization of state control mechanisms by public authorities to improve the overall quality of public services. Attention is focused on the need for effective state control to increase the level of satisfaction and well-being of citizens at the local level. A model of comprehensive implementation of state control mechanisms over the quality of public services of local self-government bodies was developed.
Keywords: public administration; state control; public services; quality of services; mechanisms; local self-government bodies